2009
DOI: 10.1016/j.ssc.2009.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Premature switching in graphene Josephson transistors

Abstract: We investigate electronic transport in single layer graphene coupled to superconducting electrodes. In these Josephson transistors, we observe significant suppression in the critical current I c and large variation in the product I c R n in comparison to theoretic predictions in the ballistic limit. We show that the depression of I c can be explained by premature switching in underdamped Josephson junctions described within the resistively and capacitively shunted junction (RCSJ) model. By considering the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…We notice that the superconducting gap (2D B1 meV) appears to be rather strongly suppressed compared with the estimation from the transition temperature (D(0) ¼ 1.764 k B , T c B1.8 meV). The gap reduction had been previously observed in Josephson weak links, including graphenebased Josephson weak links 17 . Pd appears to have significant effect in reducing the gap size 18 .…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…We notice that the superconducting gap (2D B1 meV) appears to be rather strongly suppressed compared with the estimation from the transition temperature (D(0) ¼ 1.764 k B , T c B1.8 meV). The gap reduction had been previously observed in Josephson weak links, including graphenebased Josephson weak links 17 . Pd appears to have significant effect in reducing the gap size 18 .…”
Section: Resultssupporting
confidence: 63%
“…For a critical current of B100 nA, this gives GB1. It has been demonstrated in diffusive graphene Josephson weak links at millikelvin temperatures (when Go o1) that the supercurrent is reduced through a premature switching process 3,17,27 . For stronger thermal fluctuation, however, phase diffusion dominates and causes a finite voltage in the supercurrent regime as well as gradual switching 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we investigate the Josephson current in a gapped graphene-based superconductor/barrier/superconductor (S/I/S) junction. The fabrication of superconductor on graphene is created by contacting the superconducting electrodes as mostly using aluminum (Al) electrodes [8][9][10]. The Josephson effect in graphene-based junction is observed in the Dirac fermionic behavior through a gate control [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The Josephson effect in graphene-based junction is observed in the Dirac fermionic behavior through a gate control [11][12]. The gate-tunable effect can be indicated to the switching current and is led to the application of superconducting electronic devices [10,12]. We concentrate on the gate-tunable supercurrent under the effect of thick barrier limit.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in Ref. [16] the reduction of the critical current and variations in the product I C R N were experimentally observed and theoretically explained considering non-negligible the thermal fluctuations. Other authors 3,17 suggested a supercurrent reduction by premature switching induced by thermal and electromagnetic noise.…”
Section: Introductionmentioning
confidence: 99%